Leveraging Artificial Intelligence for Sustainable Agriculture in India: Exploring Opportunities and Overcoming Challenges - Amol Pawar, Anupa (Journal of Neonatal Surgery, 2025)
Abstract The use of AI technologies is transforming agricultural practices across the globe. AI can cut radically into productivity in India, where farming is critical to its economy and where much of its people must be fed. The paper analyses the advantages and challenges of `AI-powered technologies for sustainable agriculture in India. With the help of advanced IoT devices, machine learning, computer vision AI tech, it can further improve a multitude of farming processes such as precision agriculture, pest management, irrigation and yield forecasting to name a few. These technologies can make Indian farmers climate-change ready, reduce chemical usage and make supply chain efficient. However, adoption of these technologies remains low as they are expensive, farmers lack digital literacy, early-stage tools.